2022
DOI: 10.1111/vox.13367
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of therapeutic plasma exchange in severe COVID‐19 disease: A meta‐analysis

Abstract: Background and Objectives Therapeutic plasma exchange (TPE) has been used in severe COVID‐19 disease to eliminate the cytokine storm. This meta‐analysis aims to assess the effectiveness of TPE in reducing mortality in severe COVID‐19 disease compared to standard treatment. Materials and Methods A comprehensive literature search was performed in PubMed, the Cochrane database and the International Clinical Trial Registry Platform (ICTRP). The random‐effect model was used to calculate the risk ratio and standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Our meta-analysis demonstrates a significant reduction in short-term mortality when adjunct TPE is added to the standard therapy of critically ill patients with sepsis-induced organ dysfunction. These findings, combined with those of three recently published meta-analyses [66][67][68] add to the current body of evidence reflected in the 2023 ASFA guidelines which allow TPE to be considered on a case to case basis for sepsis with multiple organ dysfunction (category III, 2A recommendation) [41]. In addition, a large propensity-score matched analysis [69] demonstrating reduced 28-day and 1-year mortality associated with TPE in septic patients with MODS was published in November 2023, but was not included in the current analysis so as to avoid deviations from the predefined protocol and to avoid bias.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our meta-analysis demonstrates a significant reduction in short-term mortality when adjunct TPE is added to the standard therapy of critically ill patients with sepsis-induced organ dysfunction. These findings, combined with those of three recently published meta-analyses [66][67][68] add to the current body of evidence reflected in the 2023 ASFA guidelines which allow TPE to be considered on a case to case basis for sepsis with multiple organ dysfunction (category III, 2A recommendation) [41]. In addition, a large propensity-score matched analysis [69] demonstrating reduced 28-day and 1-year mortality associated with TPE in septic patients with MODS was published in November 2023, but was not included in the current analysis so as to avoid deviations from the predefined protocol and to avoid bias.…”
Section: Discussionmentioning
confidence: 57%
“…However, prospective, randomized data are scarce and inconclusive [35,36]. Previous attempts to clarify have resulted in five meta-analyses [37][38][39][40][41] with the authors of these analyses concluding there is insufficient evidence to recommend TPE as routine therapy for patients with sepsis-induced organ dysfunction. Currently, the American Society for Apheresis (ASFA) 2023 guidelines [42] provide a category III, 2A recommendation for the use of TPE for patients with sepsis-induced organ dysfunction, allowing for individualized use on a case-by-case basis.…”
Section: Introductionmentioning
confidence: 99%
“…14,20 The results of a meta-analysis indicated that TPE can reduce mortality in severe COVID-19 but with no change in ICU length of stay. 21 TPE has also been successfully used for the treatment of inflammatory syndromes after SARS-CoV-2-infections in adults and children. 14,22 As a result, many authors consider TPE to be the last therapeutic resort when standard (immunomodulatory) therapy fails.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TPE is one of the therapies suggested for PIMS or severe SARS-CoV-2 infections when other therapeutic options fail 14,20 . The results of a meta-analysis indicated that TPE can reduce mortality in severe COVID-19 but with no change in ICU length of stay 21 . TPE has also been successfully used for the treatment of inflammatory syndromes after SARS-CoV-2-infections in adults and children 14,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of this approach is that it triggers a significant, albeit transient, decrease in thrombo-inflammatory blood molecules without inducing immunosuppression. If implemented in the early stages, this strategy could improve thrombo-inflammation in patients with severe COVID-19 by replacing inflammatory molecules and accumulated activated haemostatic factors with healthy plasma components, thereby delaying or preventing ICU admission ( 21 ). The ongoing Therapeutic Plasma Exchange to Alleviate the Hyperinflammatory Condition During Severe Covid-19 Infections (CovidEP) trial (ClinicalTrials Identifier: NCT04751643) addresses this issue and assesses the requirement for intubation and invasive ventilation in patients undergoing 3 TPE sessions in 3 consecutive days compared to patients receiving standard treatments including assisted ventilation, oxygen supplementation, non-invasive ventilation, vasopressive support and corticosteroids, etc.…”
Section: Introductionmentioning
confidence: 99%